PRINSIP, MEKANISME DAN BENTUK PELAYANAN INFORMASI KEPADA PUBLIK OLEH DIREKTORAT JENDERAL PAJAK (Lex Jurnalica, 2020)
Public information disclosure is the government's responsibility in realizing good governance. The existence of transparency of public information about the performance of the government in carrying out the administration of the state or its government, allows the public to actively participate in controlling every step and policy taken by the government. This paper will look at the principles, mechanisms and forms of information services to the public? and what is the form of the provision of public information services by the Directorate General of Taxes? The method used is a qualitative research method with conceptual research based on existing literature. The principles, mechanisms and forms of information service to the public are already running according to the rules in the Public Information Openness Act. The right to obtain this information is a human right and the openness of public information is one of the important features of a democratic country that upholds the sovereignty of the people to achieve good state administration. For the provision of public services by the Direktorat Jenderal Pajak (DJP), the disclosure of public information carried out by the DJP has gone well. This can be seen from the number of community requests in point A amounting to 34, and the response from the DJP which is also 34.